(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
The inevitability of change is a universal constant. Ever since the first industrial revolution science and technology has played a pivotal role in shaping our lives and lifestyles. The integration of technology with finance ultimately led to the creation of the fintech industry. Fintech today has played a vital role in determining the production, consumption, income, investment, and savings pattern of individuals and society. This dissertation deals with a few ways in which digital payment platforms can be a boon or bane for society as whole. The study analyses the perception of different categories of users of digital payment platforms. A survey was conducted among 230 users of digital payment platforms belonging to different demographics. The purpose of the survey was to analyse the perceptions and attitudes of the different categories of users using exploratory factor analysis. The study also explains the effect of overspending induced by digital transaction platforms on the economy and understands the effectiveness of digital transaction platforms to achieve the Sustainable Development Goals (SDGs).